Nation-building, Belonging and Multiculturalism in Indonesia: Contextualising Ibn Khaldun’s Theories and Beyond - Widiyanto, Asfa (İbn Haldun Çalışmaları Dergisi, 2018)
This paper strives to reread and recontextualise the ideas of Ibn Khaldun on diversity, group feeling and political legitimacy, most specifically within the contemporary context of nation-state. Ibn Khaldun states, “A dynasty rarely establishes itself firmly in lands with many different tribes and groups”. A high level of diversity (with no social cohesion), is regarded as a peril rather than a promise, most particularly to the stability of the state or dynasty. This paper address the following problems: (a) what societal cultures which contribute to the Indonesian nation-building; (b) how do the minority groups perceive their belonging to the nation and how do they respond to the nation-building.